Online assessment of learning outcomes: the experience of Poland - Wornalkiewicz, W.; Diachenko, O.; Haranzha, O. (Scientific notes of the pedagogical department, 2021)
The epidemiological situation and periodic restrictions imposed in Poland in 2020-2021 forced universities to quickly transform off-line learning into distance one. For this reason, the offered standard e-learning platforms and/or the created own implemented internet access applications were used. Full-fledged distance learning at a university has also become possible thanks to recording the students’ grades in their electronic indexes. The article analyses the process of organizing the assessment of students' knowledge in Polish universities. The situation of online assessment was considered on the example of the Faculty of Economics and Pedagogy, the Academy of Management and Administration in Opole. The place of the lecturer's thematic blog in the preparation of students' final works was also analysed. The authors argue that the experience of a Polish university can be used in organizing the assessment of students' learning outcomes in Ukrainian universities and secondary schools.